y'=
=
Находим производную.
Найдём критические точки, приравняя производную к нулю. ОДЗ незабудем:
Вложение.
x=1 - точка максимума.
y'=![(11+6\sqrt{x}-2x\sqrt{x})'=(11)'+(6\sqrt{x})'-((2x)'\sqrt{x}+(\sqrt{x})'(2x))=](/tpl/images/0169/7907/25d44.png)
=![\frac{3}{\sqrt{x}}-2\sqrt{x}-\frac{x}{\sqrt{x}}=\frac{3-2x-x}{\sqrt{x}}=\frac{3(1-x)}{\sqrt{x}}](/tpl/images/0169/7907/69d4d.png)
Находим производную.
Найдём критические точки, приравняя производную к нулю. ОДЗ незабудем:![x\geq0](/tpl/images/0169/7907/6e2de.png)
Вложение.
x=1 - точка максимума.